Rezension von: Risch, Izhak, Megillath Mishpachtenu - Ulshöfer, Kuno (Württembergisch Franken, 1985)
Izhak Risch: Megillath Mishpachtenu. Records conceming the ancestry of the Levi, Berlinger and Ellinger families of the Zvi branch (in Ivrit). Haifa 1974. 88 S.